Mystagogy in Daily Experiences: A Spiritual-Theological Understanding of Mystagogy - Budi Wibowo, Antonius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
Mystagogy has been recognized as an archaic word which was revived and developed after the Second Vatican Council. The Council begins to facilitate some pastoral concerns on the baptism for adults. The meaning of mystagogy is even more enlarged not only in the scope of liturgical teachings and rites of initiation. It also covers daily life of the faithful in every age and society. This article will present how the dynamic application of the mystagogical process helps clarify the connection between mystagogy and daily experiences of the faithful. Mystagogy is still ‘at work’ and continues to develop in the praxis of faith. Inspired by some theological approaches, the second part of this writing will discuss the connection between mystical sense and daily experience. The author will portray the relations ‘between the mystagogue and the myste’ and ‘between the myste and God’ towards the mystery of faith, before exploring mystagogy in daily experiences within the contexts of mystery and self-transcendence. An extended application of this reinterpretation will be offered in the last section to lead towards transformation through the daily experiences. Key Words:*Mystagogy *Catechesis *Pedagogy *Discipleship *The myste *Mystical experience *Daily life experience *Transformation *Self-transcendence *Spiritual journey.